O movimento dos atingidos por barragens e o enfrentamento de desastre ambiental: uma aproximação prática da educação ambiental e do campo - Valdanha Neto, Diógenes; Jacobi, Pedro Roberto (Ambiente & Educação: Revista de Educação Ambiental, 2020)
Este artigo relata estudo desenvolvido no contexto de inundação, no ano de 2014, da comunidade ribeirinha de São Carlos do Jamari, no estado de Rondônia. O objetivo principal foi o de compreender a atuação educacional do Movimento dos Atingidos por Barragens (MAB) nessa situação. Desenvolveu-se um estudo de caso entrevistando e realizando grupo focal com lideranças do MAB. Os resultados permitem concluir que o MAB teve forte impacto como agente educativo no contexto estudado, utilizando diversas estratégias descritas na literatura da Educação Ambiental e do Campo para a efetivação de suas ações. As decorrências foram repercutidas principalmente em duas grandes categorias: a transformação da relação da comunidade consigo mesma (comunidade-comunidade), e da comunidade com o Estado. The movement of peo-ple affected by dams and the overcoming of environmental disaster: a practical proximity of environmental and rural education This paper presents a research developed in the context of the 2014 flooding of the riverside community of São Carlos do Jamari, in the state of Rondônia. The main objective was to understand the educational performance of the e Movement of People Affected by Dams (MAB) in this situation. A case study was developed interviewing and conducting focus group with MAB leaders. The results lead to conclude that MAB had a strong impact as an educational agent in the studied context, using several strategies described in the Environmental and Rural Education literature for the development of its actions. The outcomes were mainly reflected in two main categories: the transformation of the relationship of the community with itself (community-community), and of the community with the State. Keywords: Social Learning. Social movements. Traditional Communities. Rural Education. Sustainability.